A blow-up result for a nonlinear damped wave equation in exterior domain: The critical case. (1st June 2017) - Fino, A.Z.; Ibrahim, H.; Wehbe, A.
Abstract: We consider the initial boundary value problem of the nonlinear damped wave equation in an exterior domain Ω . We prove a blow-up result which generalizes the result of non-existence of global solutions of Ogawa and Takeda (2009). We also show that the critical exponent belongs to the blow-up case.